2014
DOI: 10.1038/pr.2014.197
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular dysfunction in adult mice following postnatal intermittent hypoxia

Abstract: Our results suggest that exposures to postnatal IH alter the normal development of the renin-angiotensin system and promote the occurrence of cardiovascular dysfunction during adulthood in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
0
27
0
1
Order By: Relevance
“…The long term physiological effects of IH during the neonatal period have been studied extensively in rodent models (810), but few studies have focused on brain development and/or injury, or on brain inflammation. However, two studies in mice have indicated that early postnatal exposure to relatively mild IH report biochemical and electron microscopy evidence for a decrease in myelination possibly due to impaired myelinogenesis, impaired axonal maturation, short and long term neuro-functional deficits and electrophysiological changes that may form the basis for more long-term neurobehavioral sequelae (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…The long term physiological effects of IH during the neonatal period have been studied extensively in rodent models (810), but few studies have focused on brain development and/or injury, or on brain inflammation. However, two studies in mice have indicated that early postnatal exposure to relatively mild IH report biochemical and electron microscopy evidence for a decrease in myelination possibly due to impaired myelinogenesis, impaired axonal maturation, short and long term neuro-functional deficits and electrophysiological changes that may form the basis for more long-term neurobehavioral sequelae (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the IH-exposed mice also exhibited impaired vasodilatory responses to acetylcholine, and endothelial cells that were harvested from their mesenteric arteries expressed higher levels of angiotensin-converting enzyme (ACE) and reactive oxygen species, along with elevated plasma angiotensin-II (AGT) levels. Furthermore, increased DNA methylation patterns of the ACE1 and the AGT genes were apparent in the endothelial cells of the IH-exposed mice 113 .…”
Section: Studies On Obstructive Sleep Apnoea In Children and Epigenetmentioning
confidence: 92%
“…It is now well established that premature birth, and possibly the presence of apnoea of prematurity, are accompanied by an increased risk of cardiovascular and metabolic disease during adulthood [110][111][112] . To further examine the viability of the epigenetic hypothesis, we exposed neonatal mice to IH, and then allowed them to recover in normoxia till they reached adulthood 113 . IH-exposed mice manifested evidence of endothelial dysfunction, as shown by reduced reperfusion indices after tail vessel occlusion indicating abnormal flow mediated vasodilation.…”
Section: Studies On Obstructive Sleep Apnoea In Children and Epigenetmentioning
confidence: 99%
“…22,23 A study 24 using a mouse model of postnatal chronic intermittent hypoxia demonstrated persistent elevated systolic blood pressure, impaired baroreflex, decreased heart Elevated glucocorticoid levels have been associated with increased blood pressure.…”
Section: Postnatal Factors Hyperoxia and Hypoxia In Premature Infantsmentioning
confidence: 99%
“…24 These studies suggest that for a premature infant, postnatal exposures may be as important as prenatal environment for the programming of cardiovascular disease. There is a desperate need for more research in this area to identify modifiable exposures in neonatal intensive care to optimize long-term outcomes in these patients.…”
Section: E258mentioning
confidence: 99%